(untitled) (SCIENCE TIME JOURNAL, 2025)
According to our analysis, it can be stated that one of the trends in curriculum development aimed at enhancing the teaching competence of novice teachers in improving students’ reading literacy is the lack of adequate institutional mechanisms to foster competitiveness in the educational environment. This indicates that the strategies for creating a competitive atmosphere in classrooms or groups have not been thoroughly explored. Improving the methodology of teaching reading literacy among novice teachers by developing a systematic approach relies on organizational trends and norms that can impact learners’ socialization. Therefore, revising the curriculum to align with contemporary trends also necessitates a reevaluation of the educational content. According to a meta-analysis of curriculum development trends focused on improving the teaching methods for enhancing reading literacy among novice teachers, it is clear that the educational content should be grounded in activities and approaches that shape and develop learners’ competence.